The Ethics of Self-Care in Caring Professions - Craig Irvine (Encyclopaideia, 2014)
The medical academy's primary ethical imperative may be to care for others, but this imperative is meaningless if divorced from the imperative to care for oneself. How can we hope to care for others if we, ourselves, are crippled by ill health, burnout, or resentment? The self-care imperative, however, is almost entirely ignored in the training of healthcare professionals. Indeed, this training opposes the introspection essential to the practice of ethical self-care. If we are to heed the self-care imperative, healthcare professionals must turn to an ethics that not only encourages, but even demands care of the self. We must turn to narrative ethics. Since narrative is central to the understanding, creation, and recreation of ourselves, we can truly care for ourselves only by attending to our self-creating stories. Narrative ethics brings these stories to our attention; so doing, it allows us to honor the self-care imperative.